Health education intervention in primary school: active breaks for the promotion of motor activity - Domenico Monacis; Dario Colella; Alessia Scarinci (Firenze University Press, 2020)
School is an ideal setting for proposing interventions aimed at increasing levels of physical activity. A systematic literature review was performed to underline the relationship between active breaks and physical, cognitive and psychological variables of primary school children. Fifteen works were selected and included in the review. The results show an increase in MVPA physical activity levels in 53% of the studies. There are limited evidences about cardiorespiratory fitness improvement, and BMI management. Some studies show an improvement in cognitive and attention factors. Active breaks represent an important opportunity to increase PAL (physical activity levels). Future researches on a rational application and proposal of active pauses are needed.   Interventi di educazione alla salute nella scuola primaria: le pause attive per la promozione dell'attività motoria La scuola costituisce un setting ideale per la proposta di interventi finalizzati all'aumento dei livelli di attività fisica. È stata eseguita una revisione sistematica della letteratura per analizzare la relazione tra pause attive e variabili fisiche, cognitive e psicologiche dei bambini della scuola primaria. Quindici lavori sono stati selezionati, analizzati ed inseriti nella revisione. I risultati evidenziano un aumento dei livelli di attività fisica MVPA (53% degli studi), un miglioramento della capacità cardiorespiratoria e della gestione del BMI. Alcuni studi evidenziano un miglioramento dell'impegno cognitivo e fattori attentivi.  Brevi pause di attività motoria rappresentano un'importante opportunità per aumentare i livelli di attività fisica (LAF) in contesto scolastico. La ricerca futura per una razionale proposta ed applicazione delle pause attive sembrerebbe essere giustificata alla luce di queste, seppur limitate, evidenze.